If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(v + -3) + -4v = 120 Reorder the terms: -8(-3 + v) + -4v = 120 (-3 * -8 + v * -8) + -4v = 120 (24 + -8v) + -4v = 120 Combine like terms: -8v + -4v = -12v 24 + -12v = 120 Solving 24 + -12v = 120 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -12v = 120 + -24 Combine like terms: 24 + -24 = 0 0 + -12v = 120 + -24 -12v = 120 + -24 Combine like terms: 120 + -24 = 96 -12v = 96 Divide each side by '-12'. v = -8 Simplifying v = -8
| 9x^2-18xy-8x+16y= | | 10x-20+7=12+6x+3 | | -5.6+8a=7a+7.6 | | -8-(-16+10)=12 | | 7x(1-4x)+5(1+2x)= | | (x^2+6x+5)+(x^2+6x+5)= | | 6x-4=16+2x | | 3/2x-y=17 | | 4m-4=rm | | 2x-6=3x+1-x-6 | | x-3/2y=13 | | -13=8m+5m | | X+(x-1)+(x+1)=90 | | 2v+3=19 | | 3(-4x)=-2(6x-9) | | 3(y-4)-4=2y+6.9 | | (-.8)(1/5)=x | | 8y=11y+3 | | w/11=3 | | 6+2(8f-2)=4(1+f) | | 6.2x-5+x-1.5=0 | | p=180*(33.333/100) | | (-4)-(-.8)=x | | (x^2+6x-4)+(-x^2-6x+4)= | | 91+(-11)= | | 5y^2+y+1y=4 | | 3/x=5/2x | | 8z+33=3(3z+11)-z | | 89=x+13(7) | | 12x^2-(121/12)=0 | | -5(x-3)=10 | | -3(2x+2)=6x-8 |